Effect of provenances on wood properties of Balfourodendron riedelianum - Vianna Assad, Amanda Aparecida; Ballarin, Adriano Wagner [UNESP]; Menezes Freitas, Miguel Luiz; Longui, Eduardo Luiz (Inst Ecologia A C, 2020)
Wood is comparatively more conservative than other parts of trees, such as leaves, which present greater phenotypic plasticity. We studied the effect of seed origin on annual increment, physical-mechanical properties and anatomical characteristics of Balfourodendron riedelianum wood in a homogeneous plantation (Luiz Antonio Experimental Station (LAES)) from three natural provenances (Galia and Baum in Sao Paulo State and Alvorada do Sul in Parana State, Brazil). Because genotypic information is a determinant of wood formation, trees were expected to develop wood structure based on their provenances. Our results demostrate that variations in volume, properties and wood anatomy were influenced by provenance. Alvorada do Sul trees showed lower growth in volume and higher strength and homogeneity, compared to Galia and Baum. Typical radial pattern was not observed for most characteristics, except modulus of elasticity and fiber length in Galia and compression parallel to the grain in Bauru that increased towards the bark. Based on the latter characteristc, B. riedelianum wood in a homogeneous planting has class C40 mechanical strength, as indicated for use in medium-sized structures, light civil construction and the manufacture of furniture.
Keywords: annual increment; guatambu; pau marfim; radial variation; strength class; tropical wood